Consequences of Delayed Endoscopies on the IBD Population during the COVID-19 Pandemic - Karen C. Young; Vitaliy Poylin (World Journal of Colorectal Surgery)
Background: During the COVID-19 pandemic, routine maintenance including endoscopies were postponed for patients with Inflammatory Bowel Disease (IBD). The effects of delaying endoscopies on IBD outcomes are currently unknown. Objectives: This study aimed to evaluate effects of delayed endoscopies on IBD patients. Design: Retrospective study. Patient and Methods: review of all IBD patients scheduled for routine endoscopy at Northwestern Memorial Hospital March 13, 2020 through May 31, 2020, during which all endoscopies were canceled due to COVID-19. Patients were divided between rescheduled on-time after delayed. Patient outcomes one year after cancellation were examined. Main Outcome Measure: hospital and emergency room admissions, surgery, and medication changes. Sample Size: 250 patients. Results: 100 patients were included in the delayed group and 150 in the on-time group, with mean ages of 47.5 and 42.8 years respectively. 59.2% had Crohn's disease (CD), 39.2% had Ulcerative Colitis (UC) and 1.2% had indeterminate colitis. Both groups had similar severity scores during the delay and 1 year post-endoscopy. There was no difference in the number of emergency room or hospital admissions during the delay or at one-year post-endoscopy. One-year post-endoscopy there were significantly more hospitalizations in the on-time group (n=14, 9.3%) compared to the delayed group (n=3, 3%), P=0.03. There were more IBD related surgeries in the on-time group (16) compared to the delayed group (4), P=0.03. Conclusion: Patients with delayed endoscopies due to COVID-19 did not experience worse outcomes compared to patients with on-time endoscopies. There was a higher number of admissions and operations in the on-time group despite similar severity scores. Limitations: Retrospective analysis, only short and intermediate term follow up. Conflict of Interest: None.